DOP33 Single-cell analysis identifies pathological fibroblasts as a new therapeutic target to prevent intestinal fibrosis in Crohn's disease. (30th January 2023) - Ke, B J; Abdurahiman, S; Biscu, F; Verstockt, S; Verstockt, B; de Hertogh, G; Vermeire, S; Matteoli, G
Abstract: Background: Recurrent episodes of intestinal inflammation and tissue remodeling progressively result in fibro-stenosis and bowel obstruction in Crohn's disease (CD). This irreversible end-stage complication is the main indication for surgical intervention but is often associated with postoperative recurrence of inflammation and repeated tissue resection. Methods: To understand transmural inflammation-induced fibro-stenosis, full-thickness ileum from CD patients (n=10) undergoing ileocecal resection were profiled using single-cell RNA sequencing (scRNA seq) on 10x Genomics platform. Our tissue sampling strategy aimed at recapitulating different disease stages from the same patient including normal ileum, chronic active inflammation and stenotic ileum, allowing a better definition of cell heterogeneity, inter-cellular communication, and tissue organization in CD. Healthy ileum from CRC patients (n=5) undergoing right hemicolectomy were included as external control. Flow cytometry (FACS) was carried out to confirm scRNA seq findings. For functional validation, intestinal fibroblasts were co-cultured with NicheNet-predicted cytokines and FACS-sorted myeloid supernatants. Finally, the chronic dextran sulfate sodium (DSS)-induced colitis model was used to validate the transcription regulation in activated fibroblasts. Results: Using scRNA seq, we identified a specific subset of activated fibroblasts during chronic inflammation and fibrosis. FACS showed increasing FAP+ fibroblasts in both inflamed and stenotic ileum, compared to control ileum and proximal ileum (p<0.01). Computational methods predicting ligand-receptor signaling suggest that fibroblast activation is mostly mediated by myeloid cell-derived inflammatory signals resulting in collagen deposition and tissue fibrosis. Intestinal fibroblasts co-cultured with inflammatory monocyte supernatant and predicted ligands expressed higher protein levels of FAP, COL3A1 and showed signs of EMT transformation. Furthermore, stimulated intestinal fibroblasts secreted higher levels of ECM proteins, including COL1 (p<0.001), and COL3A1 (p<0.005). After inhibiting an EMT-related transcription factor identified in the activated fibroblasts, collagen expression and extracellular matrix accumulation were decreased in fibroblasts. Finally, inhibition of EMT transformation in chronic DSS colitis resulted in reduced ECM deposition, compared to vehicle mouse (p<0.05). Conclusion: Our findings suggest that inflammatory monocytes mediate local activation of fibroblasts promoting excessive collagen deposition. We furthermore show that targeting activated fibroblasts was able to reduce tissue remodeling and may therefore prevent fibrostenosis in CD.